Efficacy and safety of iron supplementation in patients with heart failure and iron deficiency: a meta-analysis. Issue 8 (20th February 2019) - Zhang, Shuo; Zhang, Fengxiao; Du, Meng; Huang, Kun; Wang, Cheng
Abstract: Fe therapy can be effective in heart failure patients both with and without anaemia. However, the role of Fe therapy in such patients is still uncertain. In this review, the aim was to evaluate the efficacy and safety of Fe therapy in adult patients with heart failure who have reduced ejection fraction (HFrEF). Multiple databases (PubMed, Medline, EMBASE, the Cochrane Library and Clinical Trials) were searched up to December 2017 and the reference lists of relevant articles obtained from the search were reviewed. Data extracted from randomised control trials (RCT) selected for the review were pooled using a fixed effects model or a random effects model, according to heterogeneity between trials. Nine RCT were included in this meta-analysis which included a total of 789 patients who received Fe therapy and who in turn were compared with 585 controls. There was significant improvement in the 6-min walk test (19·05 m, 95 % CI 10·48, 27·62) and peak VO2 /kg (0·93 ml/kg per min, 95 % CI 0·16, 1·69) in the Fe supplementation arm. With Fe therapy, fewer patients were hospitalised for heart failure (OR: 0·42, 95 % CI 0·27, 0·65), but no relationship was found for total re-hospitalisation (OR: 0·70, 95 % CI 0·32, 1·51) or mortality (OR: 0·70, 95 % CI 0·38, 1·28). Fe therapy has the potential to improve exercise tolerance, reduce re-hospitalisations for patients with HFrEF having Fe deficiency. In addition, Fe supplementation was found to be safe, with no increased rate of adverse events.